From the Roots to the Present of Personal Financial Planning – Achievements on the 50th Anniversary of the Movement - Waliszewski, Krzysztof; Welch, H. Oliver (Journal of Finance and Financial Law, 2021)
The purpose of the article The aim of the article is to present the reasons for the emergence of personal and financial planning in the 1960s in the US, and then its quantitative and qualitative evolution around the world, taking into account institutional aspects. Methodology Review of the literature on the subject, legal acts and statistics of the financial advisory movement. Results of the research The study found that personal financial planning emerged from a grassroots initiative as a response to the needs of consumers and progressive representatives of the financial sector. Its territorial expansion beyond its homeland was associated with a growing awareness of the benefits of financial advisory services to households. Before the entire financial planning movement there is enormous growth potential.